221. A pre-absorber optimization technique for pencil beam scanning (PBS) proton therapy treatments. (December 2018) - Fracchiolla, F.; Fellin, F.; Innocenzi, M.; Lipparini, M.; Cianchetti, M.; Dionisi, F.; Vennarini, S.; Schwarz, M.
Abstract : Purpose: To design and implement a new protontherapy planning method for the treatment of shallow lesions with PBS and to compare it to the standard method. Methods: In order to treat tumors located at depths lower than our minimum range available (4.1 cm), a pre-absorber is needed (Range Shifter – RS). The RS also causes scatter, so it is associated to some dose degradation, which should be minimized. We studied three tumor localizations (pelvic, H&N and Cranio-Spinal-Irradiation) requiring RS and we created three plans for each case: one is the standard method with the RS always used as close as possible to the patient, one with the RS used only for the shallow part of the tumor but completely retracted (Figure a) and the third as the second but with the RS as close as possible to the patient (Figure b). We called these last two Range Shifter Optimization (RSO) techniques. We compared those plans in terms of dose distribution quality, delivery time and patient QA results. Results: In tables dosimetric results and delivery time are reported. A very good sparing of OARs are obtained when the RSO technique is used with the RS extended toward the patient with no significative loss in terms of target coverage. Patient QA gave very good results in terms of γ Passing Rate (PR) (3%, 3 mm) for both RSO techniques (mean 98.09%, minimum 93.75%) while the standard had some very low PR (minimum 81.09%) while the average was still good (97.73%). The delivery time increased but was still acceptable in terms of patient compliance. Conclusions: We developed a new planning technique for shallow lesions and we demonstrated its superiority (plan quality and patient specific QA results) with respect to the standard method. This technique is now routinely used to treat patients in our centre.